Addressing Legal Liability Issues in Cases of Harm due to Agricultural Genetically Modified Organisms (GMOs): Does current liability law find a suitable balance between the injuring and injured party? - Roschauer, Oliver (Department of Public Law, 2014)
In 1973, the first creation of recombinant bacteria, E. coli, allowed for gene engineering. After this development, it was possible to create a genetically modified organism (GMO) by adding a new gene into an organism's genome. A short time after this invention, the commercial value of these genetically modified products was discovered which resulted in the establishment of biotechnology companies. Nowadays, GMOs have a wide application in biological and medical research, production of pharmaceutical drugs, experimental medicine and agriculture.